Readiness to Transition to Online Learning: A Survey among Filipino Pre-service Teachers - Nurfaiza Joe; Juspher Handang; Kathleen Gregorio; Lyka Saldariega (International Journal on Integrated Education, 2022)
This study is focused on the perspective of readiness to transition to online learning of the pre-service teachers who are currently enrolled in Western Mindanao State University during the COVID-19 Pandemic. Quantitative research design was employed in this study and adapted a descriptive survey method. 311 pre-service teachers coming from different year level and majors responded to the said survey. Through the use of statistical software SPSS, the collected data was analyzed. The findings of this study unveiled that the perception of pre-service teachers’ readiness towards online learning is high. It was revealed that the motivation of the pre-service teachers is high. Amidst the urgent shift of learning to online, it was shown that the level of readiness of pre-service teachers is high as they are confident in operating the basic functions of Microsoft Office programs and managing the internet and software which are essential skills for online learning contexts. Albeit, learners need to acquire a sense of control. Learner control ranked the lowest along with online communication self-efficacy ranking second to the last. The prominent issue of the intermittent connection as well as the electric power interruptions has been a long issue and governments need to take a serious action toward this dilemma. Moreover, teachers should stimulate the learners’ online/communication self-efficacy in a way that students will participate in discussions, sharing ideas, and expressing their opinions.